(untitled) (Research, Society and Development, 2023)
Pesticides are synthetic chemicals widely used in agriculture to control pests and diseases. The predominant model of agriculture in Brazil is based on the excessive use of these products and currently the country occupies the first place in the world ranking of consumption. Despite enabling the growth of agricultural production, the excessive use of pesticides has consequences for human health and the environment. The objective of this study was to evaluate the possible toxic, cytotoxic and genotoxic effects of the insecticide cyromazine using the Allium cepa bioassay. Healthy onion bulbs were exposed to different insecticide dosages, in addition to positive and negative controls, for a period of five days. After which, a macroscopic analysis was performed to assess toxicity, counting the number of germinated roots and the length of the three largest roots of each bulb. For the evaluation of cytotoxicity and genotoxicity, slides were made for analysis of cells in different phases of the cell cycle. The tested insecticide was toxic to A. cepa, inhibiting germination and root growth at different verified concentrations. Furthermore, cytotoxic effects were observed at the two highest concentrations analyzed. The compound was considered genotoxic, as it induced chromosomal aberrations and micronuclei in cells, especially at higher dosages. The study contributed with relevant information about the toxicity and genotoxicity of the insecticide cyromazine in A. cepa, but also indicates the need for additional research in other test organisms.